THICKNESS PLANNING FOR RIGID PAVEMENT OF REACH STACKER LANES IN THE CONTAINER YARD AREA OF EX-JICT 2, TANJUNG PRIOK PORT, PT PELABUHAN INDONESIA - Fuad Ardian Nurudin; Fatchur Rahman; Anasya Arsita Laksmi; Fadhil Muhammad Nuryanto; Winnie Yudhitia Hapsari (Universitas Udayana, 2025)
This research discusses the planning of Reach stacker routes in the Ex-JICT 2 Container Yard area of the Tanjung Priok Port, PT Pelabuhan Indonesia. The background of this research is the increasing need for port efficiency to support domestic and international goods distribution. Reach stackers were chosen due to their flexibility in moving containers, however, the movement of this equipment requires routes that meet standards to ensure safety and efficiency. This research uses a structural design method for port pavement designed to withstand Reach stacker loads for 20 years using Interpave, British Precast Standard. The analysis includes wheel loads, wheel proximity factors, dynamic loads, and optimal pavement thickness. The results show that C35/45 concrete material is more recommended than C32/40 with a fiber steel mixture and C8/10 CBGM pavement with CBP, as it has higher compressive strength and better resistance to heavy loads.